KRISIS HARGA MINYAK DUNIA DAN KINERJA PORTOFOLIO SAHAM PERUSAHAAN PERKEBUNAN INDONESIA - Anam, Khoirul; Kusumawati, Nur Farida; Purwanto, Fajar; Ambarika, Ni Dewi (Berkala Ilmiah AGRIDEVINA, 2020)
This study aims to compare the stock portfolio of plantation companies and their performance in the period before and after the crisis of world oil prices. The research method uses the single index model to form a stock portfolio and the index of sharpe, treynor and jensen to measure its portfolio performance. The research uses secondary data of plantation companies listed in the Indonesian Stock Exchange from July 2012 to June 2016. The results showed that there were two plantation company stocks categorized as portfolio candidates in the period before the crisis of world oil prices, namely PT. Astra Agro Lestari Tbk. (AALI) and PT. Tunas Baru Lampung, Tbk. (TBLA), while in the period after the crisis of world oil prices portfolio stocks cannot be established. The stock portfolio of plantation companies in the period before the crisis of wortd oil prices have a higher rate of return and performance index compared to after the crisis of world oil prices. Investors who want to invest in the stock market are advised to make a selection and form an optimal stock portfolio. Investors should observe the movement of stock prices if occur a crisis situation in the national and global levels. DOI : https://doi.org/10.33005/adv.v9i1.2210